Antimicrobial Stewardship for Ventilator Associated Pneumonia in Intensive Care (the ASPIC trial): study protocol for a randomised controlled trial. Issue 2 (21st February 2023) - Foucrier, Arnaud; Roquilly, Antoine; Bachelet, Delphine; Martin-Loeches, Ignacio; Bougle, Adrien; Timsit, Jean-François; Montravers, Philippe; Zahar, Jean-Ralph; Eloy, Philippine; Weiss, Emmanuel
Abstract : Introduction: Ventilator-associated pneumonia (VAP) remains the leading cause of infections treated in the intensive care units (ICU). In a personalised care approach, we hypothesise that the duration of treatment of VAP can be reduced in function of the response to treatment. Methods and analysis: The Antimicrobial Stewardship for Ventilator-Associated Pneumonia in Intensive Care (ASPIC) trial is a pragmatic national multicentre, phase III, non-inferiority, comparative randomised (1:1) single-blinded clinical trial. Five hundred and ninety adult patients hospitalised in 24 French ICU with a microbiologically confirmed first episode of VAP that received appropriate empirical antibiotic therapy will be included. They will be randomly allocated to standard management with duration of appropriate antibiotic fixed for 7 days according to international guidelines or antimicrobial stewardship based on daily clinical assessment of clinical cure. The assessment of clinical cure will be repeated daily until at least three criteria of clinical cure are met, allowing the discontinuation of antibiotic therapy in experimental group. The primary endpoint is a composite endpoint combining of all-cause mortality measured at day 28, treatment failure or new episode of microbiologically confirmed VAP until day 28. The aim of the study is to demonstrate that a strategy to reduce the duration of antibiotic therapy for VAP based on clinical assessment is safe could lead to changes in practice as part of a personalised therapeutic approach, by reducing exposure to antibiotics and their side effects. Ethics and dissemination: The ASPIC trial has been approved by the French regulatory agency (Agence Nationale de Sécurité du Médicament et des Produits de Santé, ANSM; EUDRACT number 2021-002197-78, 19 August 2021) and an independent ethics committee the Comité de Protection des Personnes Ile-de-France III (CNRIPH : 21.03.25.60729, 10 October 2021) for the study protocol (version ASPIC−1.3; 03 September 2021) for all study centres. Participant recruitment is scheduled to begin in 2022. Results will be published in international peer-reviewed medical journals. Trial registration number: NCT05124977 .